2014
DOI: 10.14260/jemds/2014/3983
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in Patients Treated Under RNTCP in Karad Tuberculosis Unit

Abstract: BACKGROUND: The Revised National Tuberculosis Control Programme (RNTCP), India. OBJECTIVE: To study the treatment outcomes in patients treated under RNTCP &causes of defaulted, death, failure among them. MATERIAL & METHODS: This study was conducted in Karad Tuberculosis Unit (TU), Satara District, Maharashtra. Under Karad Tuberculosis Unit there were nine PHCs, Sub District Hospital and Krishna Hospital, six Designated Microscopy Centre's (DMC), three Integrated Counseling and Testing Centre's (ICTC)-KH, SDH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
2
Order By: Relevance
“…In the present study during course of treatment 4 patients (1.9%) were LFU, 3 patient transferred out, 1 patient shifted to private treatment, 6 patients (2.9%) died, treatment failed in 10 patients (4.8%), 184 patients (88.5%) improved and it remained same at end of treatment. In their study Vandana Bhoi et al 6 found that out of 806 patients In our study treatment failure was high (4.8%) as compared with this study (2%), which may be due to initial heavy bacillary load. In our study 1.9% patients defaulted which is lower than Vandana Bhoi et al 6 (3.8%) & (7.7%) SL Chadha study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In the present study during course of treatment 4 patients (1.9%) were LFU, 3 patient transferred out, 1 patient shifted to private treatment, 6 patients (2.9%) died, treatment failed in 10 patients (4.8%), 184 patients (88.5%) improved and it remained same at end of treatment. In their study Vandana Bhoi et al 6 found that out of 806 patients In our study treatment failure was high (4.8%) as compared with this study (2%), which may be due to initial heavy bacillary load. In our study 1.9% patients defaulted which is lower than Vandana Bhoi et al 6 (3.8%) & (7.7%) SL Chadha study.…”
Section: Discussioncontrasting
confidence: 53%
“…In their study Vandana Bhoi et al 6 found that out of 806 patients In our study treatment failure was high (4.8%) as compared with this study (2%), which may be due to initial heavy bacillary load. In our study 1.9% patients defaulted which is lower than Vandana Bhoi et al 6 (3.8%) & (7.7%) SL Chadha study. 7 Two of our cases defaulted during intensive phase both being daily wage labourers.…”
Section: Discussioncontrasting
confidence: 53%